Processed Fluid Chemistry Data from the Ross Sea acquired during the Nathaniel B. Palmer expedition NBP0601A (2006) (IEDA: Marine-Geo Digital Library, 2006)
This data set was acquired with a Niskin Bottle Fluid Sampler during Nathaniel B. Palmer expedition NBP0601A conducted in 2006 (Chief Scientist: Dr. Walker Smith). The data files are in XLS format and include Fluid Chemistry data that has not been processed. The data was acquired as part of the project called Interannual Variability in the Antarctic - Ross Sea (IVARS): Nutrients. Funding was provided by NSF grants: ANT00-87401.